2021
DOI: 10.1038/s42003-021-02401-w
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale phenotyping of 1,000 fungal strains for the degradation of non-natural, industrial compounds

Abstract: Fungal biotechnology is set to play a keystone role in the emerging bioeconomy, notably to address pollution issues arising from human activities. Because they preserve biological diversity, Biological Resource Centres are considered as critical infrastructures to support the development of biotechnological solutions. Here, we report the first large-scale phenotyping of more than 1,000 fungal strains with evaluation of their growth and degradation potential towards five industrial, human-designed and recalcitr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 50 publications
1
8
1
Order By: Relevance
“…In accordance with our findings, Barratt et al (2003) observed that PUR degradation in soil was driven primarily by fungi. PUR degradation was previously reported for the genera Penicillium ( Brunner et al, 2018 ), Pseudogymnoascus (synonym Geomyces ; Barratt et al, 2003 ; Cosgrove et al, 2007 ), Pseudomonas ( Cregut et al, 2013 ), Rhodococcus ( Akutsu-Shigeno et al, 2006 ), and Verticillium ( Navarro et al, 2021 ). However, to our knowledge this is the first report of Impranil ® degradation by the bacterial genera Amycolatopsis , Collimonas , Kribbella , Psychrobacter, and Streptomyces and by the fungal genera Lachnellula , Neodevriesia, and Thelebolus .…”
Section: Discussionmentioning
confidence: 77%
“…In accordance with our findings, Barratt et al (2003) observed that PUR degradation in soil was driven primarily by fungi. PUR degradation was previously reported for the genera Penicillium ( Brunner et al, 2018 ), Pseudogymnoascus (synonym Geomyces ; Barratt et al, 2003 ; Cosgrove et al, 2007 ), Pseudomonas ( Cregut et al, 2013 ), Rhodococcus ( Akutsu-Shigeno et al, 2006 ), and Verticillium ( Navarro et al, 2021 ). However, to our knowledge this is the first report of Impranil ® degradation by the bacterial genera Amycolatopsis , Collimonas , Kribbella , Psychrobacter, and Streptomyces and by the fungal genera Lachnellula , Neodevriesia, and Thelebolus .…”
Section: Discussionmentioning
confidence: 77%
“…Apparently, metabolically versatile pathogens such as Phoma and Fusarium [78][79][80] drive plastisphere assembly based on trophic interactions as 'keystone plastic degraders'. By coopting their repertoire of degradative traits 78,80 to modify or degrade polymer components (i.e., 'exaptative plastibiome'), these pathogens may facilitate co-colonisation, co-degradation and co-metabolisation of MP by other members of the community, as previously described for other substrates 81,82 , ultimately enabling plasticlastic commensalism and syntrophy. It has been shown that some microbes can completely degrade, assimilate, and mineralise at least certain plastics under experimental conditions [83][84][85] , a feat that is yet to be observed in nature.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Oligotrophy: fungi were classified as 'oligotrophic', if they met any of the criteria described by Gostinčar et al 120 , including growth in extremely nutrient-poor natural habitats and environments, such as rock surface or subsurface, Arctic dry valleys, deserts, and high mountain areas; growth in (oligotrophic) anthropogenic habitats such as monuments, concrete walls, biofilters and other indoor habitats; growth on silicon, metals, glass and on a variety of more or less durable organic surfaces, including plastic materials and similar polymers; or biodegradation of complex, non-natural compounds, such as phenolic hydrocarbons, TNT, radioactive materials, plastics, etc. 54,[78][79][80] . All other fungi were classified as 'non-oligotrophic'.…”
Section: Meta-analysismentioning
confidence: 99%
“…Compared to bacteria, fungi are preferable because they have a higher tolerance to environmental toxins based on their diverse ecosystem-related traits [42]. The bioremediation of organic contaminants by different ligninolytic fungal species has been widely studied [15,43], but the capability of bioremediation within species is hardly investigated. We used a model compound, azo dye, to compare the fungal-decolorization capacity and screen a library of 320 fungal isolates across 74 species.…”
Section: Discussionmentioning
confidence: 99%